2007
DOI: 10.1128/jvi.02182-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Twelve Genomes of Three Novel Group 2c and Group 2d Coronaviruses Reveals Unique Group and Subgroup Features

Abstract: Twelve complete genomes of three novel coronaviruses-bat coronavirus HKU4 (bat-CoV HKU4), bat-CoV HKU5 (putative group 2c), and bat-CoV HKU9 (putative group 2d)-were sequenced. Comparative genome analysis showed that the various open reading frames (ORFs) of the genomes of the three coronaviruses had significantly higher amino acid identities to those of other group 2 coronaviruses than group 1 and 3 coronaviruses. Phylogenetic trees constructed using chymotrypsin-like protease, RNA-dependent RNA polymerase, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
317
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(336 citation statements)
references
References 37 publications
16
317
1
2
Order By: Relevance
“…Two genomes each of TV1, TV2 and TV3 were amplified and sequenced using strategies we previously used for complete genome sequencing of other picornaviruses and coronaviruses, with the RNA extracted from the alimentary specimens as templates Woo et al, 2005Woo et al, , 2006aWoo et al, , 2007aWoo et al, , 2009. The RNA was converted to cDNA by a combined randompriming and oligo(dT)-priming strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Two genomes each of TV1, TV2 and TV3 were amplified and sequenced using strategies we previously used for complete genome sequencing of other picornaviruses and coronaviruses, with the RNA extracted from the alimentary specimens as templates Woo et al, 2005Woo et al, , 2006aWoo et al, , 2007aWoo et al, , 2009. The RNA was converted to cDNA by a combined randompriming and oligo(dT)-priming strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Ten years after the identification of the SARS coronavirus, many other groups that jumped into the field after the outbreak of SARS have left, while the teams at the University of Hong Kong continued to make major contributions to the field. The recently identified group 2c human coronavirus EMC associated with one severe and two fatal cases of respiratory syndrome in Saudi Arabia was most closely related to two bat coronaviruses identified by Hong Kong scientists in 2007 (Woo et al, 2007;Zaki et al, 2012). Thus, the findings obtained by scientists at the University of Hong Kong have shaped the field of coronavirus research for years to come.…”
mentioning
confidence: 97%
“…Dis Aquat Org 90: [113][114][115][116][117][118][119][120] 2010 crochiropteran bat hosts; and Group 2d, from megachiropteran bat hosts (Woo et al 2007). It has been proposed that Group 3 be divided as follows: Groups 3a, from avian hosts; Group 3b, which contains a coronavirus from a beluga whale Delphinapterus leucas, the only coronavirus identified in a marine mammal to date; and Group 3c, which contains viruses from diverse avian hosts as well as one from an Asian leopard cat Prionailurus bengalensis that may represent recent host switching (Woo et al 2009).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The genus Coronavirus has been divided into 3 groups (González et al 2003). It has been proposed that Group I be subdivided into Groups 1a and 1b (Woo et al 2007); Group 1a has only been found in laurasiatherian mammal hosts, primarily those from the Carnivora, whereas Group 1b has been found in both laurasiatherian and euarchontoglire mammal hosts. It has been proposed that Group 2 be divided into the following groups: Group 2a, which has been found in both laurasiatherian and euarchontoglire mammal hosts; Group 2b, which contains SARS and viruses from microchiropteran bats; Group 2c, from mi-crochiropteran bat hosts; and Group 2d, from megachiropteran bat hosts (Woo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation